2009
DOI: 10.1603/029.102.0357
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cry1Ac and Cry1F <I>Bacillus thuringiensis</I> Insecticidal Proteins in Selected Transgenic Cotton Plant Tissue Types

Abstract: The amount of Cry1Ac δ-endotoxin in transgenic Bacillus thuringiensis Berliner (Bt) or Bollgard cotton varies among commercial cultivars. These differences in expression have been correlated with survival levels in Lepidoptera, indicating that all Bollgard cultivars do not provide the same level of control. The objective of this study was to determine if differences in overall expression among commercial cultivars of Bollgard cotton were under simple genetic control. These findings could influence the way bree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 33 publications
4
14
1
10
Order By: Relevance
“…However, unlike our results showing similar seasonal declines of about threefold in Cry1Ac and Cry2Ab in DP 164 B2RF, previous studies with other cultivars found that the seasonal decline in toxin concentration was generally less for Cry2Ab (35)(36)(37) than Cry1Ac (38)(39)(40)(41)(42). In any case, seasonal declines in the concentration of Bt toxins could be an important factor affecting redundant killing because there is extensive variation among cotton cultivars in patterns of production of Bt toxins (43).…”
Section: Discussioncontrasting
confidence: 98%
“…However, unlike our results showing similar seasonal declines of about threefold in Cry1Ac and Cry2Ab in DP 164 B2RF, previous studies with other cultivars found that the seasonal decline in toxin concentration was generally less for Cry2Ab (35)(36)(37) than Cry1Ac (38)(39)(40)(41)(42). In any case, seasonal declines in the concentration of Bt toxins could be an important factor affecting redundant killing because there is extensive variation among cotton cultivars in patterns of production of Bt toxins (43).…”
Section: Discussioncontrasting
confidence: 98%
“…The study findings are consistent with the Mendelian inheritance of a single dominant locus such as the Cry1Ab gene. In addition, these results suggest that in the leaf tissues, expression of the concentration of Bt δ-endotoxins was inherited stably and follows the Mendelian segregation as observed in the crosses of Bt maize events and the non-Bt F 2 generations (Siebert et al, 2009;Mugo et al, 2011). In the contrast analysis, crosses between Bt and nonBt F 1 generations had no significant effect on the mean concentration of Bt δ-endotoxins.…”
Section: Discussionmentioning
confidence: 54%
“…The effectiveness and sustainability of Bt transgenic technology in the control of stem borers will depend on the levels of expression of the Bt δ-endotoxins (Kranthi et al, 2005;Olsen et al, 2005;Dong and Li, 2007;Siebert et al, 2009). In addition, gene expression levels should be sufficient in appropriate plant tissues and express in successive generations (Kranthi et al, 2005;Olsen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The data used describe the season-long pattern of Cry1F and Cry1Ac expression and distribution for WideStrike cotton grown over 13 location-years in representative upland cottongrowing regions in the United States and Australia [34][35][36]. These data describing mean expression by location-year were considered to be independent and identically distributed and therefore were combined by tissue type and growth stage to generate the grand mean and range of Cry1F and Cry1Ac tissue concentrations.…”
Section: Protein Expression and Environmental Loadmentioning
confidence: 99%